Kebijakan Proteksi Anak Jalanan di Kota Yogyakarta Menurut Perspektif Maqasid Syariah - Khoirul Ummatin (Ulul Albab: Jurnal Studi dan Penelitian Hukum Islam, 2019)
The problem of street children is a social problem that often occurs in urban areas. We may often meet many children who are on the streets. Such a scene is influenced by a number of factors that cause children to suffer in life on the streets, such as family financial difficulties or pressure from poverty, parental disharmony, and special problems regarding the relationship between children and parents. The existence of street children is often a problem for various parties both from family, community and government. In overcoming the problem, the Yogyakarta city government contributed to provide a solution by issuing regional regulations related to the handling of street children, the regulation considers many aspects such as replacing repressive approaches or forced withdrawal then becoming a humane (persuasive) approach to achieving mutual prosperity. By referring to these objectives, it is appropriate to implement a policy that needs to be based on the concept of maqasid sharia which is a study of Islamic law in establishing a law that must be accompanied by goals which are shar'i (human benefit).